A representação da ditadura militar nos filmes brasileiros longa metragem de ficção : de 1964 a 2010 - Stigger, Helena Maria Antonine (2011)
This thesis analyses the representation of the military dictatorship in the Brazilian fiction feature films from the military coup of 1964 until 2010. We evidence that three elements symbolically represent the military government: the torture, the military and the militant of the armed left wing. As from this premise, we studied the variations and the possibilities of the Brazilian military dictatorship representation during those four decades by analyzing how the cinematographic speech is presented on the narrative. The methodology used was the filmic analysis of a sample composed by twenty-four movies produced between 1979 and 2010. However, we show that the military dictatorship has been represented since its beginning on cinema. Thus, we focused on studying three titles that belong to the Cinema Novo movement: O desafio, Terra em transe and Os inconfidentes. Therefore, it was possible to make a comparison between these films themes and the productions posterior to the Amnesty Law, assisted by Jean-François Lyotard s cinema studies, Hannah Arendt s violence and Ismail Xavier s allegory. From this analysis, we could understand that the movies made after 1979 basically represent the military dictatorship years between 1964 and 1974, because around 1973 the left wing organizations had already been dismantled by the government. Then, it was possible to identify that torture was a constant in those films, and to portray it, the narratives used a more conventional esthetic.